2001
DOI: 10.1590/s1519-566x2001000300017
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Thiamethoxam on Entomopathogenic Microorganisms

Abstract: Efeito do Tiametoxam Sobre Microrganismos EntomopatogênicosRESUMO -A compatibilidade de microrganismos entomopatogênicos com tiametoxam e outros inseticidas foi estudada através de ensaios in vitro e em campo. Os microrganismos testados foram: Aschersonia aleyrodis, Bacillus thuringiensis, Baculovirus anticarsia (VPNAg), Beauveria bassiana, Hirsutella thompsonii, Metarhizium anisopliae, Nomuraea rileyi, Paecilomyces farinosus, Sporothrix insectorum e Verticillium lecanii. Em laboratório, foram testadas duas co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
0
23

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(51 citation statements)
references
References 10 publications
3
25
0
23
Order By: Relevance
“…The compatibility of M. anisopliae with thiamethoxam and lambdacyhalothrin is in agreement with other studies (Batista Filho et al, 2001;Cavalcanti et al, 2002;Loureiro et al, 2002;Neves et al, 2001;Rampelotti-Ferreira et al, 2010). Despite the insecticide thiamethoxam+ lambdacyhalothrin is a combination of two compatible insec- ticides, it was scored as moderately toxic in this study.…”
Section: Discussionsupporting
confidence: 92%
“…The compatibility of M. anisopliae with thiamethoxam and lambdacyhalothrin is in agreement with other studies (Batista Filho et al, 2001;Cavalcanti et al, 2002;Loureiro et al, 2002;Neves et al, 2001;Rampelotti-Ferreira et al, 2010). Despite the insecticide thiamethoxam+ lambdacyhalothrin is a combination of two compatible insec- ticides, it was scored as moderately toxic in this study.…”
Section: Discussionsupporting
confidence: 92%
“…Batista Filho et al (2001) reported that imidacloprid did not affect M. anisopliae at the maximum dose recommended for the field but inhibited fungal growth at the minimum dose, thus classifying this insecticide as moderately toxic to the fungus at the maximum dose and incompatible at the minimum dose. However, no toxicity of imidacloprid to M. anisopliae was observed by Loureiro et al (2002), and Neves et al (2001) showed that the product did not inhibit germination, radial growth or fungal reproduction.…”
Section: Commercial Namementioning
confidence: 99%
“…Different techniques can be used to evaluate the effects of chemical products on spores of B. thutingiensis subsp. thuringiensis (Btk) such as paper disks impregnation technique with broth products (DOUGHERTY; REICHELDERFER; FAUST, 1971;JIMENEZ;ACOSTA;FERNANDEZ, 1989) and with liquid culture medium (SUTTER et al, 1971, CHEN et al, 1974, and mixing products to the molten culture medium technique from the works of Salerno, Dias and Sagardoy (1999), Batista Filho; Almeida and Lamas (2001), Almeida et al (2003) and Gassen, Batista Filho and Zappelini (2006). The effects of chemical products on Btk using different techniques was studied by Silva et al (2006Silva et al ( , 2008 and the results varied according to chemical group, technique used, concentration, contact time, and development stage of the pathogen.…”
Section: Introductionmentioning
confidence: 99%